Primary squamous cell carcinoma and adenocarcinoma simultaneously occurring in the same lung lobe: a case report and literature review - Zhang, Tianyu; He, Ruyuan; Xiao, Yongguang; Geng, Qing (Frontiers in Oncology, 2024)
The co-occurrence of distinct lung cancer types within the same lobe is an exceedingly rare phenomenon. Here, we present a unique case wherein primary invasive squamous cell carcinoma and invasive adenocarcinoma concurrently manifested in the identical lung lobe. Additionally, we provide a comprehensive overview of the diagnosis and treatment approaches for multiple primary lung cancers, along with highlighting existing challenges based on the most recent guidelines. Our case underscores the importance of sampling each lesion individually, conducting separate diagnostic procedures, and determining the histological subtype for effective treatment planning irrespective of their location or size.